Photophysical and Photoacoustic Properties of π‐Extended Curcumin Dyes. Effects of the Terminal Dimethylamino Electron‐donor and the Bridging Aryl Ring1. (17th August 2018) - Borg, Raymond E.; Hatamimoslehabadi, Maryam; Bellinger, Stephanie; La, Jeffrey; Mithila, Farha; Yelleswarapu, Chandra; Rochford, Jonathan
Abstract: The synthesis, photophysical and photoacoustic characterization for a series of nine π ‐extended quadrupolar curcumin dyes is presented. A systematic evaluation of the π ‐bridging unit including the p‐ phenyl, naphth‐4‐yl, thien‐2‐yl and hybrid 4‐naphthathien‐2‐yl groups is presented. Furthermore, evaluation of the strongly donating donor‐ π ‐acceptor‐ π ‐donor quadrupolar dimethylamino terminated derivatives is also included. Select dyes exhibit excited state absorption at increased laser fluence which translates to the production of a nonlinear enhanced photoacoustic response. In particular, the bis‐4‐dimethylaminonaphtha‐2‐thien‐5‐yl curcuminBF2 contrast agent DMA‐5 exhibits an excellent molar photoacoustics (PA) emission at both low (9.4 × 10 3 V M −1 ) and high (1.47 × 10 5 V M −1 ) laser fluence which is confirmed by its strong contrast by photoacoustic tomography (PAT). In summary, the strong absorbance and enhanced photoacoustic properties of naphthyl and thienyl curcuminoids here presented provides great promise for future photoacoustic imaging applications as demonstrated by preliminary PAT studies. Abstract : The synthesis, photophysical and photoacoustic characterization for a series of donor‐ π ‐acceptor‐ π ‐donor quadrupolar dimethylamino terminated curcumins is presented. Select dyes exhibit excited state absorption which translates to a nonlinear enhanced photoacoustic response. In particular, the bis‐4‐dimethylaminonaphtha‐2‐thien‐5‐yl curcuminBF2 contrast agent exhibits an excellent molar PA emission at both low and high laser fluence which is confirmed by its strong contrast by photoacoustic tomography.